2022
DOI: 10.1071/cp21493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environments and cultivars on grain ionome of spring wheat grown in Kazakhstan and Russia

Abstract: Kazakhstan–Siberian Network on Spring Wheat Improvement unites 18 spring wheat (Triticum aestivum L.) research and breeding programs and presents opportunities to study genotype × environment interactions. Trial data from six locations in Kazakhstan and Russia in 2017–18 were used for grain ionomics analysis to evaluate the relative contributions of environment and genotype to variation in elemental composition and to formulate a methodology to enhance concentrations of important minerals in grain. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The series of ionomics studies with spring wheat in the region allows the development of a breeding strategy and methodology to enhance the elemental composition. Two previous ionomics studies in Northern Kazakhstan and Western Siberia [14,15] demonstrated a large effect of protein content on the concentration of both macro-and microelements. Concentrations of Fe, Mn, and S were positively correlated with protein content on both environment and genotype levels.…”
Section: Breeding Approaches Based On the Study Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…The series of ionomics studies with spring wheat in the region allows the development of a breeding strategy and methodology to enhance the elemental composition. Two previous ionomics studies in Northern Kazakhstan and Western Siberia [14,15] demonstrated a large effect of protein content on the concentration of both macro-and microelements. Concentrations of Fe, Mn, and S were positively correlated with protein content on both environment and genotype levels.…”
Section: Breeding Approaches Based On the Study Resultsmentioning
confidence: 92%
“…The analysis of genotype by environment interactions for the KASIB trials showed that genetic improvement for all elements would be highly affected by the uniformity of experimental fields [14]. Broad sense heritability values demonstrated substantial variation between sites and years for all elements.…”
Section: Breeding Approaches Based On the Study Resultsmentioning
confidence: 99%
See 3 more Smart Citations